The asymmetric effect of institutional quality on Chinese outward real estate investment - Zhang, Jingjing; Lee, Chyi Lin; Chan, Nelson (International Journal of Strategic Property Management, 2019)
Chinese outward investment in real estate (FDIRE) has increased tremendously in recent years. However, it has attracted little attention in the literature. This study aims to assess the asymmetric impact of institutional quality on Chinese outward FDIRE using an extended gravity model with a real estate institutional factor. Using the unique dataset of Chinese outward real estate investment collected from Real Capital Analytics, we identify the main determinants of China’s outward FDIRE. The results show that the established gravity model and real estate institutional factor together explain China’s outward FDIRE. Specifically, market size and cultural proximity have a positive influence on the FDIRE outflows from China. In addition, institutional factor, namely real estate transparency, has an acute impact on China’s outward FDIRE, whilst it is conditional on the market size of and the economic growth speed of a country, highlighting an asymmetric effect of institutional quality on Chinese outward FDIRE. The implications of the findings have also been discussed.